Plasma and urine pharmacokinetics of intravenously administered flunixin in greyhound dogs. Issue 5 (14th May 2019) - Morris, Tim; Paine, Stuart W.; Zahra, Paul; Li, Eric; Colgan, Sally; Karamatic, Steven
Abstract: Medication control in greyhound racing requires information from administration studies that measure drug levels in the urine as well as plasma, with time points that extend into the terminal phase of excretion. To characterize the plasma and the urinary pharmacokinetics of flunixin and enable regulatory advice for greyhound racing in respect of both medication and residue control limits, flunixin meglumine was administered intravenously on one occasion to six different greyhounds at the label dose of 1 mg/kg and the levels of flunixin were measured in plasma for up to 96 hr and in urine for up to 120 hr. Using the standard methodology for medication control, the irrelevant plasma concentration was determined as 1 ng/ml and the irrelevant urine concentration was determined as 30 ng/ml. This information can be used by regulators to determine a screening limit, detection time and a residue limit. The greyhounds with the highest average urine pH had far greater flunixin exposure compared with the greyhounds that had the lowest. This is entirely consistent with the extent of ionization predicted by the Henderson–Hasselbalch equation. This variability in the urine pharmacokinetics reduces with time, and at 72 hr postadministration, in the terminal phase, the variability in urine and plasma flunixin concentrations are similar and should not affect medication control.